COVID-19 cutaneous manifestations in children and adolescents: a systematic review - Pasquini Neto,Ricardo (2022)
ABSTRACT Objective: The aim of this study was to evaluate the coronavirus disease 2019 (COVID-19) cutaneous manifestations described in pediatric patients and discuss their relevance for early diagnosis. Data source: The study consisted of a systematic review of original articles indexed in PubMed and Embase databases, as well as gray literature articles found through Google Scholar. A search strategy, based on PICO (Patient, Intervention, Comparison, Outcome) Tool, with the terms “child,” “infant,” “childhood,” “adolescents,” “teenagers,” “COVID-19,” “SARS-CoV-2,” and “skin manifestations,” was performed to optimize the findings. The study did not restrict any article regarding language. Data synthesis: Out of the 310 articles that initially met the inclusion criteria, 35 were selected for review, totalizing 369 patients. The most common COVID-19 cutaneous manifestations in children and adolescents were Chilblain-like lesions, presented in 67.5% of the cases, followed by erythema multiforme-like (31.7%) and varicella-like lesions (0.8%). The Chilblain-like lesions appeared 7.6 days (95%CI 7.4–7.8) after the viral infection and lasted for 17.5 days (95%CI 16.5–18.5), erythema multiforme-like lesions appeared in 9.5 days (95%CI 9–10) and lasted for 10.3 days (95%CI 9.1–11.5), and varicella-like lesions appeared in 12.3 days (95%CI 4–20.6) and lasted for 7 days. Conclusions: Knowledge of the different skin manifestations in children and adolescents with COVID-19 is essential for an early diagnosis and, consequently, the possibility of promptly care adoption as well as to interrupt the new coronavirus transmission chains in the current pandemic context.